The Use of Multi-Walled Carbon Nanotubes and Nanoclay for Simultaneously Improving the Flame Retardancy and Mechanical Properties of Epoxy Nanocomposites - Tuan Anh, Nguyen; Quang Tung, Nguyen; Trong Phuc, Bach; Xuan Canh, Nguyen (International Journal of Engineering and Technology, 2018)
In this study, the flame retardants epoxy nanocomposites were prepared by combining mechanical stir and sonication of epoxy Epikote 240 (EE240) resin, chlorinated paraffin, atimony oxide, multi-walled carbon nanotubes (MWCNTs) and montmotillonite clay. Resultants of CNTs, montmorillonite and flame retardant additives were investigated limiting oxygen (LOI) and UL-94, combustion rate. The SEM, FE-SEM, TEM were measured to analyze the dispersion of MWCNTs and montmorillonite clay in epoxy matrix. The mechanical properties including tensile strength, compressive strength, flexural strength and impact strength Izod were studied. The results of testing burning and mechanical properties indicated that CNTs were more efficient than clay in improving the flame retardancy of materials. The dispersion method combining of mechanical stir and sonication is the good choice to distribute additive agents into epoxy matrix.Â Â